Bildung und Partizipation Mitbestimmung von Schülerinnen und Schülern in Deutschland, Österreich und der Schweiz - Quenzel, Gudrun; Beck, Michael; Jungkunz, Sebastian (Verlag Barbara Budrich, 2023)
Democracy has to be learned and lived - school is the ideal place for this. This book shows where pupils in Germany, Austria and Switzerland can have a say in their schools and how they learn tolerance, empathy and self-efficacy in the process. The study reveals that participation usually takes place outside of the classroom, although young people are particularly interested in greater involvement in classroom topics.